2017
DOI: 10.1128/mbio.00240-17
|View full text |Cite
|
Sign up to set email alerts
|

Phage Inhibit Pathogen Dissemination by Targeting Bacterial Migrants in a Chronic Infection Model

Abstract: The microbial communities inhabiting chronic infections are often composed of spatially organized micrometer-sized, highly dense aggregates. It has recently been hypothesized that aggregates are responsible for the high tolerance of chronic infections to host immune functions and antimicrobial therapies. Little is currently known regarding the mechanisms controlling aggregate formation and antimicrobial tolerance primarily because of the lack of robust, biologically relevant experimental systems that promote n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 35 publications
3
89
1
2
Order By: Relevance
“…For example, during chronic infections spatially organized bacterial aggregates of P.a. protect themselves against phage killing by producing exopolysaccharides 30 . Furthermore, modelling efforts have shown that spatial structure affects the therapeutic success of phage therapy 31 and phage-antibiotic combination therapy 32 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, during chronic infections spatially organized bacterial aggregates of P.a. protect themselves against phage killing by producing exopolysaccharides 30 . Furthermore, modelling efforts have shown that spatial structure affects the therapeutic success of phage therapy 31 and phage-antibiotic combination therapy 32 .…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of simulations and experiments we can also make predictions about the spatial architectures of phage-host interaction that are particular to biofilm environments. Prior work from our groups and others have shown that phages can be immobilized within the biofilm matrix, where they are blocked from gaining access to otherwise susceptible cells (17,18). Our observations here indicate that whenever phage movement is limited within biofilms, it is likely that the extracellular matrix (which is modeled implicitly here as the factor controlling phage diffusion) contains phages which are blocked from host access but not necessarily inert; they remain a threat to susceptible cells after the dispersion of biofilms due to mechanical disturbance or induced by bacteria themselves after depleting local nutrient supplies (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…This process has been studied for decades, however phage resistance evolution has received little attention in the context of biofilms, in which cells adhere to surfaces and embed themselves in a secreted polymer matrix (14)(15)(16). Biofilm growth is thought to be the most common mode of bacterial life, but we are just beginning to understand the mechanistic and ecological details of phage-bacteria interaction within them (9,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations